Plan de negocios para la producción, comercialización y exportación de claveles a Polonia - Icaza Bustamante, Daniel Germánico (2021)
This project aims to develop a business plan for the production, marketing and export of carnations to Poland, begins with strategic direction, establishes mission, vision and values, organizational objectives are set, the business model, potential customers are identified , the demand is analyzed, the model of income, expenses and costs is established; and key resources. The management of human talent is defined and the profiles, functions and skills of the different positions are included. The availability of materials and supplies, the analysis of the macro and micro environment, the strengths, opportunities, threats and weaknesses are identified; the distribution channels to be used; fixed, deferred investment and working capital; competitive advantages; the price; income strategies; the study of the market that involves the analysis of macro and micro economic variables. Management and operations, marketing management, study and financial evaluation are established. Then, it is defined that the product that is going to be produced, commercialized and exported is the carnation typified as select of different colors and with quality certification, the potential clients are the importing companies of fresh flowers based in Poland. The FOB price per bundle of 25 units is established at USD2.25, digital media will be used for its promotion and the CRM Cloud platform will be used to maintain relationships with customers; the distribution channel will be: producers-agents-wholesalers-retailers-consumers, which embraces the Supplier Driven marketing model. As competitive advantages, it is proposed: maintain an attractive average price, exploit the recognition of Ecuadorian flowers in the international market, have quality certification and implement the CRM platform in the Cloud. To which is added, the efficiency of the production processes to guarantee the quality of the product. Finally, the NPV presents a positive figure, which according to the projections will exceed the minimum expected return, the IRR is greater than the opportunity cost, which shows that the project is profitabl